(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This research is aimed at determining the physicochemical parameters of wells in southern Kaduna. In order to help the people of the study area to understand how to use these wells sustainably, and also to provide information to organizations like WHO, UNICEF and UNDP that are concerned with water quality in improving and monitoring performance to enable better planning and management at the national level. This was achieved by determining, physical and chemical characteristics of the wells water. The samples were taken from five Local Governments in the area using a base map. The water samples were collected using American Standard procedure of sample water collection. The laboratory analysis revealed a significant level of chemical contamination as well as differences in the concentration level of the physical and chemical parameters of the samples within the study area and the World Health Organization Standard of 2014. pH, electrical conductivity, total dissolved solid, total hardness, alkalinity and chloride were within the permissible level of the World Health Organization 2014 while salinity, turbidity suspended solid were above the permissible level of WHO 2O14 in some samples. Therefore proper waste disposal, treatment of the contaminated water, proper sitting of wells and public enlightenment were recommended.